Delayed presentation of enterocutaneous fistula after tubal ligation: a case report - Munnamgi, Sinduja; Singh, Sudhir Kumar; Huda, Farhanul; Ravikumar, Arundev; Gajula, Bhargav (International Surgery Journal, 2020)
A 50-year-old woman with a history of tubal ligation nine years earlier, presented with a complaint of discharge from the scar site. She was found to have an enterocutaneous fistula. The patient underwent an exploratory laparoscopy. The tract excised and primary repair of bowel done. A unique feature of the case is the formation of an enterocutaneous fistula after an extremely long latency due to gauze threads, which has not been previously reported in the literature.